Comparing hard coral cover between Panggang and Kelapa Island Administrative Village, Seribu Islands National Park, Indonesia. (March 2019) - Fahlevy, K; Prabowo, B; Mubarok, M W I; Fahrezil, F Y; Abdurrahman, M I; Prasetial, M F; Wicaksono, R Z; Aprizan, M; Subhan, B; Madduppa, H
Abstract: The existence of coral communities as a critical components have been highly threatened. Marine national park as a part of the marine protected areas (MPAs) has been established to protect the diversity of the coastal ecosystem. However, the hard coral communities within the national park are consistently degraded. It is important in assessing the coral cover at the national park to provide the natural pattern of coral community structures. The aims of this study were to compare the coverage of coral and dead coral with algae cover at two different reef depths (crest and slope) among two administrative villages (Panggang and Kelapa Island) within the Seribu Islands National Park, Indonesia. Overall, the hard coral cover percentage in Kelapa and Panggang Islands was higher in reef crest. The highest percent cover in the Kelapa (45.25 ± 2.61%) were higher than Panggang (26.86 ± 2.58%) Islands. In terms of dead coral with algae (DCA), percent cover at Kelapa (30.25 ± 2.66%) was higher than Panggang (24.16 ± 3.14%) Islands. The different of two depths have proved to be significant predictors of hard coral and dead coral with algae between Kelapa and Panggang. A total of 52 genera belonging to 13 families of hard coral were found during this study.